ABOUT THE EXPERIENCE OF TEACHING MATHEMATICS FOR ENGINEERING SPECIALTIES IN THE FRAMEWORK OF DISTANCE LEARNING - Asmykovich, Ivan; Pyzhkova, Olha; Borkovskaya, Inna (Physical and Mathematical Education, 2021)
Formulation of the problem. The article discusses the problem of ensuring the quality of mathematical education in modern conditions. To solve this problem, it is necessary to improve both the forms and methods of teaching, and the organization of the educational process as a whole. At present, when teaching is complicated by the problem of complying with epidemiological requirements in connection with the spread of COVID-19 infection, it is necessary to make optimal use of all opportunities to ensure the proper level of mathematical training of future engineers. Materials and methods. To solve the problem, the experience of teaching mathematical disciplines at the Department of Higher Mathematics of the Belarusian State Technological University using both traditional and information and communication technologies is analyzed. The results of a survey conducted among students of the Faculty of Technology of Organic Substances of BSTU are used. Analyzed modern publications on distance learning mathematics. Results. The analysis of the state of teaching mathematics for students of engineering specialties in the Republic of Belarus is carried out. The issue of the use of classical and information and communication educational technologies in modern conditions is studied on the example of teaching mathematical disciplines, as well as the possibilities of online learning using the platforms LMS Moodle, Microsoft Teams, Zoom, etc. The disadvantages and advantages of distance learning are discussed. Conclusions. Optimal for ensuring the quality of mathematical education in modern conditions is a combination of classical approaches to teaching using information and communication technologies. The degree of assimilation of knowledge depends not so much on the form of presentation of the material by the teacher, but on the student’s motivation to study the subject. It is necessary to instill in students the skills of self-education, self-organization, independent decision-making, to instill in students the desire for self-development. Online learning should use all the opportunities for learning and building feedback with students in order to maintain the quality of education in a difficult epidemiological period.